Editorial (International Journal of Business Innovation, 2024)
With great enthusiasm, we present the third issue of Volume 3 of the International Journal of Business Innovation. This issue highlights our commitment to fostering a platform for high-quality, interdisciplinary research that addresses the evolving dynamics of the business landscape. The contributions in this issue emphasize diversity in both subject matter and methodology, showcasing the innovative efforts of scholars worldwide.In this issue, we are pleased to present three outstanding articles that explore various critical topics in contemporary business and societal contexts.The first article, “Development Trends in China's E-Commerce Research Topics: Knowledge Map Evolution in Four Planning Stages (2001-2020)” by Yu-Shen Fang and Li-Chun Fang, examines the trajectory of research on China's electronic commerce over two decades. Employing bibliometric co-citation analysis, the authors unravel the key themes driving the digital economy in China, such as artificial intelligence integration, trust factors, and cross-border collaboration. This article provides invaluable insights into how e-commerce policies and innovations have shaped China’s standing in the global marketplace.Next, the article “Parity in Management Positions in Local Public Administration in Portugal: A Case Study” by Maria Manuela Natário, Amândio Baía, and Bruna Pinto investigates gender parity within municipal governance in two Portuguese districts. By analyzing data spanning several electoral periods, the authors shed light on the progress made under the Parity Law and the persistent challenges to achieving gender equality in public administration. This study contributes significantly to ongoing discussions on equitable representation in leadership roles.Finally, “Impression Management Strategies: A Bibliometric Analysis” by Nina Santos Damas delves into the nuanced practices of impression management within organizational contexts. Utilizing bibliometric tools, this research maps the academic discourse surrounding impression management, revealing trends in publication, co-authorship networks, and thematic foci over the past decade. The findings underscore the implications of these strategies for organizational reputation and stakeholder engagement.We extend our gratitude to the authors and reviewers for their contributions, which uphold the quality and relevance of our publication. These efforts embody our mission to connect academic research with practical applications, fostering innovation. We hope this issue inspires readers and look forward to presenting more impactful studies in future issues.Rui Pedro Marques, Elisabete Vieira, Graça Azevedo, and Susana Marques Editorial Team
Keywords: editorial